Impact of COVID-19 awareness on health-related behavior among adolescents in Nepal - Banstola, Bidhya; Dhungana, Durga (Journal of Gandaki Medical College-Nepal, 2021)
Introduction: With occurrence of COVID-19, many countries have initiated lockdown in an effort to control the pandemic. These measures can only be effective when the people co-operate. The awareness and health-related behavior have a major role in determining society’s response. Meanwhile adolescents are at the risk of deviating from disciplined health-related behaviors due to turbulence arising from their hormones despite of their awareness. This study aims to study COVID-19 awareness and its impact on health-related behavior of adolescents. Methods: A descriptive cross-sectional web-based online study of 299 adolescents enrolled in various educational programs, between ages 13 to 19 years was conducted between June 18, 2020 and July 11, 2020 in Nepal. The questionnaire consisted of demographic characteristics, 16 items on knowledge and 40 items on behavior. Descriptive statistics, chi-square tests and binary logistic regression were conducted in Statistical Package for the Social Sciences. Results: A total of 299 adolescents were enrolled in the study. Majority (92.6%) of the adolescents had adequate awareness. Positive health-related behavior was seen in 72% of the adolescents. Spiritual behavior was the most affected in comparison to physical, social and psychological behavior. Adolescents with adequate awareness on COVID-19 were 10.67 times more likely to perform positive health related behavior (P=0.005; 95% CI=2.01-56.47). Conclusion: Majority of the adolescents had adequate awareness. Significant percentage of adolescents had positive health-related behavior. Positive behaviour was not proportionately in level with adequate awareness. Effective health programs and policies are needed to transform adequate awareness into positive health-related behaviour for effective control of disease.